De la mécanique du bonheur à la mécanique de la mort : Réflexions critiques sur quelques paradigmes du développement - Schwarz, Alf (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
Just as reflection on international development is suffering from a certain shortness of breath, so are the dynamics of technico-industrial growth becoming weaker. This study seeks to demonstrate how this double falling off originates in the weaknesses manifest in the energy reasonings of the mechanical logic which latter directs the ideology and the material basis of economic and social development. After having first summarized the classical'paradigm of mechanical growth, the study recapitulates the principal argumentation of the theoretical model of the thermodynamicists of development and of their critique of the classical paradigm. The study also stresses how both eliminate from their analyses of the process of the economic ans social development of nations that human energy of the unexpected and the contradictory that is born of the meeting of multiple historical experiences, of the impacting of the « similar » and the « different » and which produces, as the ultimate mutation, the ecumenical history of the international dynamic. The perspective brought to the area of study may be summarized therefore by this question both so simple and at the same time so complicated: how does one sustain the diversity of cultures, respect the experience of Others, live with them without reducing them to silence, without co- opting them, without thinking that all the roads of History lead toward us.